Ergonomics in laparoscopic surgery: a work system analysis to reduce work-related musculoskeletal disorders across surgeons in Peruvian hospitals - Escobar-Galindo, C. Manuel (2023)
Laparoscopic surgery, also called minimally invasive surgery, is a type of surgery in which the surgeon operates by viewing the surgery on a screen that projects images from a camera inserted into the patient's abdomen. Laparoscopic tools are long (usually up to 35 cm) and require fine motor skills and visual perception for manipulation, restricting the degrees of freedom to move within the patient. This restriction causes surgeons to operate with limited vision and restricted movement and force them to work with assistants who assist in conducting the cameras, acting as "the surgeons' eyes". Because of its minimally invasive nature, laparoscopic surgery is well accepted by patients but is challenging and complex for the surgeon. This is due to the restriction of movement and perception that forces surgeons to adopt awkward postures with high exposition, which increases the likelihood of work-related musculoskeletal disorders (WRMSD). WRMSDs are detrimental to surgeons' health and potentially may impact patient safety. Studies often highlight the problems of surgeons in high-income countries, whose solutions and clinical guides often cannot be applied to countries like Peru, which have severe deficiencies in its healthcare system. For this reason, the thesis proposes a contextualised investigation of the Peruvian surgical work system to investigate the main factors contributing to the development of WRMSD in laparoscopic surgeons, which may affect patient safety. The analysis aimed to propose possible recommendations to support redesigning the laparoscopic surgery work system in Peruvian hospitals. Five studies were developed to achieve the aims based on the Systems Engineering Initiative for patient safety model, an ergonomics model for healthcare systems analysis. The first three studies were developed parallel with a mixed convergent design approach concluding in an integrating study. The last two studies (study four and five) had a quantitative approach.